2021
DOI: 10.1111/ppc.12760
|View full text |Cite
|
Sign up to set email alerts
|

Perceived social support, mental health, and marital satisfaction in multiple sclerosis patients

Abstract: Purpose This study aimed to examine the patients' perceived social support, mental health, and marital satisfaction. Design and Methods Data were collected via Patient Information Form, Barthel Index of Activities of Daily Living, Marital Life Scale, Multidimensional Scale of Perceived Social Support, and General Health Questionnaire for 72 patients. Findings Multiple sclerosis (MS) patients had a moderate level of marital satisfaction. The perceived social support showed positive correlation with marital sati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 76 publications
(154 reference statements)
0
3
0
Order By: Relevance
“…However, both perceived support and positive experiences are related to the broader aspects of social relationships. For example, both received support and perceived support availability are related to how close the individual feels to their support provider (Mazer & Thompson, 2011) and their satisfaction with the relationship (Lorenzo et al, 2018; Özen et al, 2021). This issue is related to a broader need to establish what aspects of social relationships (e.g., positive experiences, perceived availability of support, perceived closeness) are most important for personal well-being (Holt-Lunstad et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, both perceived support and positive experiences are related to the broader aspects of social relationships. For example, both received support and perceived support availability are related to how close the individual feels to their support provider (Mazer & Thompson, 2011) and their satisfaction with the relationship (Lorenzo et al, 2018; Özen et al, 2021). This issue is related to a broader need to establish what aspects of social relationships (e.g., positive experiences, perceived availability of support, perceived closeness) are most important for personal well-being (Holt-Lunstad et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Cross-culturally, Kim (2010) found that support from family contributed to the marital satisfaction of Korean couples in a remarriage, whereas Ahlborg et al (2009) found that support from friends and family contributed to the marital quality of Swedish parents. Social support also positively contributed to the relationship quality of couples dealing with complex, difficult parenting and medical situations; perceived family and friend support were both predictive of marital quality for mothers of children with Autism Spectrum Disorder (Benson, 2020), and for couples with a partner with multiple sclerosis, social support was also associated with increased marital satisfaction (Özen et al, 2021). This quick snapshot of the broad application of social support on relationship quality suggests the expansive applicability, and likely fundamental role, that social support plays in shaping and contextualizing the dialogue of a romantic relationship.…”
Section: Friend and Family Support As Contextmentioning
confidence: 99%
“…MS can affect marriage satisfaction, negatively [9]. PwMS can have low or moderate level of marriage satisfaction [10,11]. In addition, it is known that depression, anxiety disorder, and sexual dysfunction negatively affect people's marriage and life satisfaction [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%